2014
DOI: 10.1089/thy.2013.0527
|View full text |Cite
|
Sign up to set email alerts
|

Papillary Thyroid Microcarcinoma Might Progress During Pregnancy

Abstract: This study is an initial report indicating that the risk of PTMC enlargement might increase during pregnancy. PTMC should be carefully followed-up for possible disease aggravation during pregnancy. Even if a PTMC enlarges during pregnancy, the patient's prognosis will probably not worsen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 20 publications
1
50
0
5
Order By: Relevance
“…These authors demonstrated a higher expression of ERa immunoreactivity in tumor samples from pregnant women than in those from controls. Two recent studies have confirmed the clinical outcome of this study but not the increased ERa expression: Shindo et al (2014) reported on the enlargement of a papillary thyroid microcarcinoma in four out of nine pregnant patients (44%). However, in all three patients who underwent surgery ER expression was not detectable.…”
Section: Er Expression and Outcome Of Thyroid Cancer In Pregnancysupporting
confidence: 85%
See 1 more Smart Citation
“…These authors demonstrated a higher expression of ERa immunoreactivity in tumor samples from pregnant women than in those from controls. Two recent studies have confirmed the clinical outcome of this study but not the increased ERa expression: Shindo et al (2014) reported on the enlargement of a papillary thyroid microcarcinoma in four out of nine pregnant patients (44%). However, in all three patients who underwent surgery ER expression was not detectable.…”
Section: Er Expression and Outcome Of Thyroid Cancer In Pregnancysupporting
confidence: 85%
“…Furthermore, there is some recent evidence for the progression of papillary microcarcinoma during pregnancy and a higher recurrence rate of thyroid cancer due to pregnancy (Messuti et al 2014, Shindo et al 2014. Results from all these studies have indicated that estrogen and its receptors are relevant to the regulation of thyroid cancer growth.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with ideal patients, patients classified as being appropriate candidates have a higher risk of disease progression (e.g., middle-aged patients) (15), child-bearing potential with or without immediate plans for pregnancy (14), or have specific characteristics that will make it more difficult to follow with observation (e.g., less than high-quality neck ultrasonography, potential of tumor multifocally in patients with a strong family history of thyroid cancer) (21), subcapsular location not adjacent to critical structures (e.g., trachea or recurrent laryngeal nerve), a potentially more aggressive molecular phenotype, or ill-defined nodule margins (22). While a disease progression rate of approximately 10% is expected in this cohort, treatment offered at the time of disease progression will still be very effective and associated with excellent clinical outcomes when these patients are followed carefully by an experienced management team.…”
Section: Rationale For Classification As An Appropriate Candidate Formentioning
confidence: 99%
“…Young patients (<40 years) were more likely to experience thyroid tumor enlargement and novel lymph node appearance compared with middle-age (40-59 years) and older patients (>60 years) (15,16). An increase in the size of the PMC was seen in four of the nine women who became pregnant while being followed with active surveillance (14). However, further studies with larger sample sizes are needed to define the impact of pregnancy accurately in very low-risk PTC.…”
mentioning
confidence: 93%
See 1 more Smart Citation